An assessment of the impact of the JSY cash transfer program on maternal mortality reduction in Madhya Pradesh, India - Marie Ng; Archana Misra; Vishal Diwan; Manohar Agnani; Alison Levin-Rector; Ayesha De Costa (Glob. Health Action, 2014)
Background: The Indian Janani Suraksha Yojana (JSY) program is a demand-side program in which the state pays women a cash incentive to deliver in an institution, with the aim of reducing maternal mortality. The JSY has had 54 million beneficiaries since inception 7 years ago. Although a number of studies have demonstrated the effect of JSY on coverage, few have examined the direct impact of the program on maternal mortality. Objective: To study the impact of JSY on maternal mortality in Madhya Pradesh (MP), one of India's largest provinces. Design: By synthesizing data from various sources, district-level maternal mortality ratios (MMR) from 2005 to 2010 were estimated using a Bayesian spatio-temporal model. Based on these, a mixed effects multilevel regression model was applied to assess the impact of JSY. Specifically, the association between JSY intensity, as reflected by 1) proportion of JSY-supported institutional deliveries, 2) total annual JSY expenditure, and 3) MMR, was examined. Results: The proportion of all institutional deliveries increased from 23.9% in 2005 to 55.9% in 2010 provincewide. The proportion of JSY-supported institutional deliveries rose from 14% (2005) to 80% (2010). MMR declines in the districts varied from 2 to 35% over this period. Despite the marked increase in JSY-supported delivery, our multilevel models did not detect a significant association between JSY-supported delivery proportions and changes in MMR in the districts. The results from the analysis examining the association between MMR and JSY expenditure are similar. Conclusions: Our analysis was unable to detect an association between maternal mortality reduction and the JSY in MP. The high proportion of institutional delivery under the program does not seem to have converted to lower mortality outcomes. The lack of significant impact could be related to supply-side constraints. Demand-side programs like JSY will have a limited effect if the supply side is unable to deliver care of adequate quality.
Keywords: Depression detection; Sentiment analysis; Deep learning; Social media; Ensemble model; Natural language processing (nlp); Feature representation; Mental health monitoring